Translation for The Readers: an Analysis on The Translation of Sean Coveyâs The 7Th Habits of Highly Effective TeenS - Prabandari, Carla Sih (LLT Journal: A Journal on Language and Language Teaching, 2012)
A good translation should be parallel with the source text both in form andÂ in meaning. Yet, because of the uniqueness of each language, parallel in form is oftenÂ difficult to achieve. This paper attempts to analyze the translation of Sean CoveyâsÂ The 7th Habits of Highly Effective Teens in terms of a sociolinguistic point of view andÂ different types of equivalence. The analysis and discussion are based on some casesÂ that I found. Based on the examples, two conclusions can be drawn. First, from theÂ sociolinguistic point of view, the use of SAYA instead of AKU to refer to the authorÂ creates more distance with the readers. Second, the translator seems to have workedÂ hard to produce a dynamic equivalence of the source text, but in some cases theÂ idiomatic expressions are not well translated. Thus, the results of the translation doÂ not sound as idiomatic as the source text.Â DOI: https://doi.org/10.24071/llt.2012.150203